Typing barrrio buyers shop in Cartagena Colombia: an analysis of cluster (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
This paper presents the results of a study in the city of Cartagena de Indias - Colombia - with the aim of analyzing the profile of buyers of consumer goods in local shops, depending on the reasons that leads to choose this as your primary care facilities: economic, cultural and commercial. For this purpose two techniques were used: one with use of bivariate F Snedecor test to establish significant differences between groups and corresponds to a multivariate nonhierarchical clustering method k-means. The analysis was using the Dyane software, version 3
Keywords: neighborhood store; retail; consumer goods